Root reconstructed with mineral trioxide aggregate and guided tissue regeneration in apical surgery: a 5-year follow-up - Bernabé, Pedro Felício Estrada [UNESP]; Azuma, Mariane Maffei [UNESP]; Ferreira, Luciana Louzada [UNESP]; Dezan Junior, Eloi [UNESP]; Gomes Filho, João Eduardo [UNESP]; Cintra, Luciano Tavares Angelo [UNESP] (FapUNIFESP (SciELO), 2013)
Apical surgery should be considered as the last treatment option and employed when conventional endodontic treatment does not provide the expected result. In teeth undergoing apical surgery, the type of retrograde filling material is one of the factors interfering with the repair of periapical tissues. The material in intimate contact with the periapical tissues plays a fundamental role in the repair process. Several materials have been studied and indicated for use in apical surgery procedures, but the mineral trioxide aggregate (MTA) is still the most frequently used one. Guided tissue regeneration (GTR) techniques have been proposed as an adjunct to apical surgery to enhance bone healing. Here is reported a clinical case in which apical surgery was performed in conjunction with MTA-based root reconstruction of the maxillary right second incisor. After the apical surgery, a root-end cavity was prepared at the vestibular face of the involved tooth and filled with MTA. A bovine bone graft and a cortical collagen membrane were placed on the bone defect. After 5 years, clinical and radiographic assessments showed that the treatment was successful. It may be concluded that MTA presents favorable characteristics in adverse conditions and can be used in conjunction with GTR in cases involving root reconstruction.

A cirurgia apical deve ser considerada como a última opção de tratamento, e realizada quando o tratamento endodôntico convencional não proporciona o resultado esperado. Em dentes submetidos à cirurgia apical, o tipo de material retro-obturador é um dos fatores que interferem no reparo dos tecidos periapicais. O material em íntimo contato com os tecidos periapicais desempenha um papel fundamental no processo de reparo. Vários materiais têm sido estudados e indicados para o uso em procedimentos de cirurgias apicais, entretanto o agregado de trióxido mineral (MTA) ainda é o mais frequentemente utilizado. A regeneração tecidual guiada (GTR) tem sido proposta como um auxiliar na cirurgia apical para melhorar a formação óssea. Aqui é relatado um caso clínico em que a cirurgia apical foi realizada em conjunto com a reconstrução radicular do incisivo lateral superior esquerdo com MTA. Após a cirurgia apical, foi preparada uma retro-cavidade na parede vestibular e o dente envolvido foi obturado com MTA. Um enxerto de osso bovino e uma membrana de colágeno cortical foram colocados no defeito ósseo. Após 5 anos, avaliações clínica e radiográfica mostram que o tratamento foi bem sucedido. Pode-se concluir que o MTA apresenta características favoráveis em condições adversas e que pode ser usado em conjunto com GTR em casos envolvendo reconstrução radicular.
Keywords: Apical surgery; MTA; Guided tissue regeneration